2018
DOI: 10.3802/jgo.2018.29.e19
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic significance of full lymphadenectomy in early-stage ovarian clear cell carcinoma

Abstract: ObjectivesThis study evaluated the therapeutic significance of full lymphadenectomy in early-stage ovarian clear cell carcinoma (OCCC).MethodsWe retrospectively reviewed records of 127 consecutive patients with pT1/pT2 and M0 OCCC who were treated between January 1995 and December 2015. We compared survival outcomes between those who did and did not undergo para-aortic lymph node dissection (PAND), and analyzed independent prognostic factors (Cox proportional hazards model with backward stepwise elimination).R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…A lack of lymph node sampling in ovarian cancer patients may play a role as well. In patients with gross intra-abdominal disease, and macroscopically normal lymph nodes, standard lymphadenectomy does not contribute to prolonged overall nor progression-free survival in these patients [ 26 27 ]. This might influence the correlation between affected lymph nodes and the risk on PM.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of lymph node sampling in ovarian cancer patients may play a role as well. In patients with gross intra-abdominal disease, and macroscopically normal lymph nodes, standard lymphadenectomy does not contribute to prolonged overall nor progression-free survival in these patients [ 26 27 ]. This might influence the correlation between affected lymph nodes and the risk on PM.…”
Section: Discussionmentioning
confidence: 99%
“…A 10-lymph node cutoff was defined as adequate lymphadenectomy according to the Gynecologic Oncology Group criteria. Several retrospective studies have demonstrated favorable survival outcomes of systematic lymphadenectomy on patients with early-stage OCCC [ 13 15 ]. In a combined exploratory analysis of three prospectively randomized phase III multicenter trials, Magazzino et al reported that lymphadenectomy offered benefit to patients with advanced OC who received complete intraperitoneal debulking [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…OCCC is of the epithelial subtype, occurring in 1-25% of epithelial ovarian cancers, and 4-10% of those presenting with lymph node metastasis. 16,17 The typical US features hematogenous metastases from extramammary malignancies to breast include oval shaped, circumscribed hypoechoic masses without calcifications or architectural distortion. 18 In this review, only 17 patients had undergone breast US examination, and the lesions presented as solid (accounting for 70.00% and 50.00% of breast lesions metastasized from all cancer types and OSCs, respectively), hypoechoic (accounting for 57.14% and 62.50% of breast lesions metastasized from all cancer types and OSCs), oval/spiculated and circumscribed/indistinct lesions without calcification (accounting for 94.11% and 90.00% of breast lesions metastasized from all cancer types and OSCs), which were summarized in Table 2.…”
Section: Discussionmentioning
confidence: 99%